2007
DOI: 10.1186/1476-069x-6-3
|View full text |Cite
|
Sign up to set email alerts
|

A community study of the effect of particulate matter on blood measures of inflammation and thrombosis in an elderly population

Abstract: BackgroundThe mechanism behind the triggering effect of fine particulate matter (PM) air pollution on cardiovascular events remains elusive. We postulated that elevated levels of PM would be associated with increased blood levels of inflammatory and thrombotic markers in elderly individuals. We also hypothesized that elevated PM would increase levels of cytokines in individuals with heart disease.MethodsWe measured these blood markers in 47 elderly individuals with (23) and without (16 COPD and 8 healthy) card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
33
0
2
Order By: Relevance
“…Other researchers demonstrated similar increases in CRP from PM10 exposure from both combustion [17] and organic matter [18]. In contrast, some studies have found only a weak or absent link between PM and markers of inflammation [19][20][21][22]. Discrepancies among studies appear related to differences in composition of PM, variable exposure to antiinflammatory medications, and differences in obtaining PM exposure data [10].…”
Section: Cardiovascular Mechanismsmentioning
confidence: 87%
See 1 more Smart Citation
“…Other researchers demonstrated similar increases in CRP from PM10 exposure from both combustion [17] and organic matter [18]. In contrast, some studies have found only a weak or absent link between PM and markers of inflammation [19][20][21][22]. Discrepancies among studies appear related to differences in composition of PM, variable exposure to antiinflammatory medications, and differences in obtaining PM exposure data [10].…”
Section: Cardiovascular Mechanismsmentioning
confidence: 87%
“…In 2007, the Women's Health Initiative Study [27] followed a cohort of over 65,000 postmenopausal women with no previous 10 Cardiovascular mortality 76% (25-147) Toren et al [29] 2007 PM Not measured Cardiovascular mortality 12% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) heart disease over approximately 6 years. The investigators revealed that long-term PM exposure in this population resulted in a 24% (95% CI, 9-41%) increase in cardiovascular events and an astonishing 76% (95% CI, 25-147%) increase in cardiovascular mortality per 10-μg/m 3 increase in PM 2.5 .…”
Section: Long-term Effectsmentioning
confidence: 99%
“…Estimated long-term traffic exposure was not related to inflammatory changes in either sex. 161 Several studies, including some with improved exposure assessment, 162 some that included analyses of large population cohorts, 163,164 and a recent evaluation of long-term annual PM 10 levels in England, 165 have not found a relationship between particulate exposure and inflammation. It is Altered HRV 111 1…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Smaller studies on cardiovascular morbidity end-points generally found little evidence for effects on sudden cardiac arrest [57], myocardial infarction [58], heart rate variability [59], and measures of systemic inflammation or thrombosis [60].…”
Section: Epidemiologymentioning
confidence: 99%